Attachment quality of children with ID and its link to maternal sensitivity and structuring. (May 2018) - Feniger-Schaal, Rinat; Joels, Tirtsa
Abstract: Background: Attachment theory produced a fertile field of research and clinical application. Although the topic of attachment of children with intellectual disability (ID) has received increasing research attention over the past 15 years, the empirical evidence is still limited. Aims: We applied theoretical and empirical knowledge of parenting typically developing children to examine the mother-child relationship in the ID population. The aim was to examine maternal sensitivity and structuring and its association with children's attachment classification and their disability. Methods: Forty preschool children (mean age 47.25, range 26–75 months) with non-specific ID and their mothers participated in the study. The mean developmental age was 25.92 months ( SD = 10.89), The DQ mean score was 55.45 ( SD = 17.28). We assessed children's quality of attachment using the SSP and maternal interactive behavior using the Emotional Availability Scales. Outcomes: Forty percent of children showed secure attachment, and 32.5% showed disorganized attachment. Attachment classifications correlated significantly with maternal sensitivity and maternal structuring but not with the child's cognitive disability. Conclusions: The results point to the importance of maternal interactive behavior for children with ID. Clinical implication may consider interventions aiming to enhance maternal sensitivity and structuring to improve children's quality of attachment.